Respuesta :

Answer:

2x-37

Step-by-step explanation:

(x+6)2-49

Step 1: Distribute

2x+12-49

Step 2: Solve

2x-37

Answer:

x=-1 so the answer is -39

Step-by-step explanation:

(28x-6)29 5E2=49 Start with the given equation.

x-6=22 22 2B-sqrt 2849 29 Take the square root of both sides.

x-6=sqrt 2849%29 or x-6=-sqrt 2849%29 Break up the "plus/minus" to form two equations.

x-6=7 or x-6=-7 Take the square root of 49 to get 7.

x=6%2B7 or x=6-7 Add 6 to both sides.

x=13 or x=-1 Combine like terms.

ACCESS MORE